Hydrophilic/Oleophilic Magnetic Janus Particles for the Rapid and Efficient Oil–Water Separation. (21st June 2018) - Song, Yongyang; Zhou, Jiajia; Fan, Jun‐Bing; Zhai, Wenzhong; Meng, Jingxin; Wang, Shutao
Abstract: The separation of microsized oil droplets from water is strongly required by the environmental protection and petroleum industry. However, the separation of microsized oil droplets from water is often ignored. Herein, magnetic Janus particles are reported with a convex hydrophilic surface/concave oleophilic surface by emulsion interfacial polymerization and selective surface assembly, realizing the rapid and efficient separation of microscaled tiny oil droplets from water. These magnetic Janus particles exhibit significant abilities to separate microscaled oil droplets from water, which usually occurs within 120 s with a separation efficiency >99%. Theoretical and experimental results demonstrate that these magnetic Janus particles can capture tiny oil droplets to make them coalesce into larger ones during the process of separation. Further studies reveal that these Janus particles can self‐assemble and closely pack onto the interface of larger oil droplets, acting as surfactants to stabilize them. Moreover, the shape effect of the Janus particle is demonstrated on the coalescence of the oil droplets. Abstract : Interfacially polymerized hydrophilic/oleophilic magnetic Janus particles can rapidly clean‐up microscale oil droplets from water. The microscaled oleophilic concave surface of the Janus particles is beneficial for capturing tiny oil droplets from water.